- pengaruh pemberian campuran madu dan kuning telur terhadap kualitas spermatozoa,fertilitas dan daya tetas ayam sentul: pengaruh pemberian campuran madu dan kuning telur terhadap kualitas spermatozoa,fertilitas dan daya tetas ayam sentul - Yustiti, Aida; Husmaini, Husmaini; Jaswandi, Jaswandi (Biospecies, 2021)
Honey end egg yolk are one of the food supplements that contain antioxidants very high.This study aims to determine the quality of sentul male spermatozoa fed honey and egg yolk before artificial insemination on the quality of spermatozoa fertility hacchability of hacching eggs.This research was conducted by an experimental method with 4 levels 0 ml honey (control),3 ml honey,5 ml honey and 7 ml honey, Factor B giving egg yolk to sentul roosters with 4 levels 0 ml egg yolk (control),3 ml egg yolk,5 ml egg yolk, end 7 ml egg yolk.The results of the study showed that based on statistical analysis it was a very significant interaction between the combination of treatment levels of honey and egg yolk administraton on semen volume(0,85%),spermatozoa motility concentration(3,92x109),motility Spermatozoa(90,00%) spermatozoa abnormalities(5,00%) ,spermatozoa fertility eggs(91,67%),embryo mortality(7%),and egg hatchability(93%).From the results of the study it can be conluded that the administration of 5 ml honey and 5 ml egg yolk significantly gives the best results.